Navigation technique in 3D information visualisation - Ibrahim N.; Noor N.F.M. (2023)
Information visualisation (IV) involves representing information visually as a mean of getting insight into data. Many techniques are available in visualising information, with city/urban planning as one of them. The challenge that lies with city/urban planning technique in Information Visualisation is how to enhance the information legibility as to assist users in their wayfinding task. Therefore, Universiti Malaya (UM) campus is used as the subject domain to study the efficiency of the city visualisation method applied to 3D virtual environment. Few navigation aids are identified and incorporated into the visualised virtual environment, and the effectiveness of these navigation aids in helping users finding the information in the 3D virtual environment, by means of navigating within it is investigated. 2004 IEEE.